NILAI RELIGIUS DAN TOLERANSI DALAM FILM ANIMASI “NUSA DAN RARA” - Alina Ningrum Sayekti; Nur Fajrie; Much. Arsyad Fardani (INOPENDAS: Jurnal Ilmiah Kependidikan, 2022)
This study aims to analyze the storyline and the meaning of religious values and tolerance, and to find out the response of children after watching the animated film "Nusa dan Rara" in interpreting religious values and tolerance in everyday life. This study uses a qualitative research type with a descriptive approach. Data collection carried out by researchers includes documentation techniques by collecting relevant sources and then analyzed using data cards. The researcher took 7 episodes including the enormity of basmallah, learn to be sincere, learn to sell, don't be extravagant, please and thank you, well it's raining and don't lose to the devil. The results showed that the animated film "Nusa and Rara" on Youtube contained religious values and tolerance in each episode. From observing this episode, students can learn to help people who are in need of help, learn to be sincere, learn to pray before doing activities, and learn to forgive. Animated films that are wrapped in daily stories in the world of children with the delivery of easy-to-understand language.